Avaliação do comportamento da IL-6 E IL-17 em ratas ováriohisterectomizadas com tratamento de melatonina - Correa, Rafaela Fortes (2021)
Technological evolution is allowing the increase of the female population over 50 years old, consequently, more women in the menopause stage bringing the consequences by this phase. According to the World Health Organization (WHO), in 1990 there were 467 million women over the age of 50 and they estimated that by 2030 there will be 1,2 billion at this age, It is known that menopause can decrease the life quality of women by enhancing the chances of infectious and inflammatory diseases such as osteoporosis, breast cancer, among others. This occurs by decreasing the synthesis of estrogen, since this hormone influences the immune system. Melatonin is a hormone that is only manufactured during nighttime and has a correlation with the immune system. In adequate concentrations, melatonin may help decrease the predisposition that menopausal women has. Therefore, this work analyzed if melatonin treatment can decrease the inflammatory mediators that cause the predisposition to diseases. This dissertation is composed of 2 chapters. The first is a review about the role of melatonin in reducing the cytokines IL-6 and IL-17 and its role in reducing the predisposition of diseases in menopause. The second chapter is the experimental study with 80 Wistar rats, 20 weeks old, evaluating if the melatonin treatment may decrease these inflammatory mediators. For that purpose, the rats were divided in 2 groups of 40 animals, 40 suffered an ovarian-hysterectomy to simulate menopause and 40 suffered a Sham surgery. After 9 weeks the melatonin treatment started. The animals with their respective surgeries were randomly divided into subgroups: control group (1H e 1S), 10mg/kg/day supplementation (2H e 2S), 20mg/kg/day supplementation (3H e 3S) and 50mg/kg/day supplementation (4H e 4S). The treatment supplementation was done by gavage for 60 days in a row between 18h to 19h. After the end of the treatment the animals were euthanized, had their blood collected to measure the amount of theses cytokines by ELISA method and identify whether melatonin was able to reduce them. The ovary-hysterectomized rats had a weight increase of 6% in relation to the sham rats, the cause of these weight increase was not determined. After the statistical analysis it was observed that there was no difference in the measurement of interleukins between the sham and ovary-hysterectomized groups. But was possible to determine that melatonin may be a possible weight reducer in female rats that simulate menopause.